Sedimentary halogens and noble gases within Western Antarctic xenoliths: Implications of extensive volatile recycling to the sub continental lithospheric mantle - Broadley, M; Ballentine, C; Chavrit, D; Dallai, L; Burgess, R (Elsevier, 2015)
Recycling of marine volatiles back into the mantle at subduction zones has a profound, yet poorly constrained impact on the geochemical evolution of the Earth's mantle. Here we present a combined noble gas and halogen study on mantle xenoliths from the Western Antarctic Rift System (WARS) to better understand the flux of subducted volatiles to the sub continental lithospheric mantle (SCLM) and assess the impact this has on mantle chemistry. The xenoliths are extremely enriched in the heavy halogens (Br and I), with I concentrations up to 1ppm and maximum measured I/Cl ratios (85.2 × 10-3) being ~2000 times greater than mid ocean ridge basalts (MORB). The Br/Cl and I/Cl ratios of the xenoliths span a range from MORB-like ratios to values similar to marine pore fluids and serpentinites, whilst the 84Kr/36Ar and 130Xe/36Ar ratios range from modern atmosphere to oceanic sediments. This indicates that marine derived volatiles have been incorporated into the SCLM during an episode of subduction related metasomatism. Helium isotopic analysis of the xenoliths show average 3He/4He ratios of 7.5±0.5 RA (where RA is the 3He/4He ratio of air = 1.39×10-6), similar to that of MORB. The 3He/4He ratios within the xenoliths are higher than expected for the xenoliths originating from the SCLM which has been extensively modified by the addition of subducted volatiles, indicating that the SCLM beneath the WARS must have seen a secondary alteration from the infiltration and rise of asthenospheric fluids/melts as a consequence of rifting and lithospheric thinning. Noble gases and halogens within these xenoliths have recorded past episodes of volatile interaction within the SCLM and can be used to reconstruct a tectonic history of the WARS. Marine halogen and noble gas signatures within the SCLM xenoliths provide evidence for the introduction and retention of recycled volatiles within the SCLM by subduction related metasomatism, signifying that not all volatiles that survive subduction are mixed efficiently through the convecting mantle. The global SCLM therefore represents a potentially important reservoir for the long term residence of subducted volatiles.